LIPASE BIJI-BIJIAN DAN KARAKTERISTIKNYA - Rofiqotus Sholeha; Rudiana Agustini (Unesa Journal of Chemistry, 2021)
Abstrak. Kebutuhan enzim sebagai biokatalis dalam bidang industri saat ini sangat tinggi. Jenis enzim yang bermacam-macam dan dari berbagai sumber telah banyak diteliti dan dikembangkan. Salah satu jenis enzim yang terus diteliti dan dikembangkan adalah lipase. Lipase adalah enzim golongan hidrolase yang mengkatalisis proses hidrolisis trigliserida menjadi gliserol dan asam lemak bebas.Lipase dapat ditemukan dalam berbagai sumber seperti pada mikroorganisme, hewan dan tumbuhan. Lipase banyak digunakan pada industri makanan, detergen, minyak, biodiesel dan farmasi. Artikel ini memaparkan beberapa aspek utama pada lipase yang berasal dari biji seperti reaksi-reaksi yang dikatalisis, karakteristik (suhu, pH, aktivator dan inhibitor), mekanisme katalisis oleh lipase serta contoh lipase biji yang telah diteliti karakteristiknya. Lipase ditemukan pada biji yang berkecambah yang berfungsi sebagai katalisator dalam proses mobilisasi lipid. Lipase memiliki kemampuan mengatalisis reaksi hidrolisis, esterifikasi, transesterifikasi, asidolisis, alkoholisis dan aminolisis dengan efisien dan stabil. Lipase dapat diklasifikasikan menjadi 3 golongan didasarkan pada kemampuannya dalam mensintesis ikatan ester yaitu lipase non spesifik, lipase spesifik 1,3 dan lipase spesifik asam lemak. Mekanisme katalisis oleh lipase melibatkan serangan nukleofilik pertama dari serin pada karbon karbonil ikatan ester menghasilkan enzim asil kovalen sebagai perantara dan melepaskan alkohol. Karakteristik biji-bijian yang telah diteliti karakteristik jenis lipase yang dihasilkan contohnya adalah African bean seed (Pentaclethra macrophylla Benth), Durian seed germination (Durio zibethinus L.), dan Biji karet (Hevea brasiliensis). Kata kunci : Lipase biji, karakteristik, mekanisme reaksi Abstract. The need for enzymes as biocatalysts in industry is currently very high. Various types of enzymes and from various sources have been widely researched and developed. One type of enzyme that is being researched and developed is lipase. Lipase is a hydrolase group enzyme that catalyzes the hydrolysis of triglycerides into glycerol and free fatty acids. Lipases can be found in various sources such as in microorganisms, animals and plants. Lipase is widely used in the food, detergent, oil, biodiesel and pharmaceutical industries. This article describes some of the main aspects of lipase derived from seeds such as catalyzed reactions, characteristics (temperature, pH, activator and inhibitor), the mechanism of catalysis by lipases and examples of seed lipases that have been investigated for their characteristics. Lipase is found in germinated seeds which functions as a catalyst in the lipid mobilization process. Lipase has the ability to catalyze hydrolysis, esterification, transesterification, acidolysis, alcoholysis and aminolysis reactions efficiently and stably. Lipases can be classified into 3 groups based on their ability to synthesize ester bonds, namely non-specific lipases, 1,3-specific lipases and fatty acid-specific lipases. The mechanism of catalysis by lipase involves the first nucleophilic attack of serine on the ester-bond carbonyl carbon producing covalent acyl enzymes as intermediates and releasing the alcohol. The characteristics of the grains that have been studied are the characteristics of the type of lipase produced, for example, African bean seeds (Pentaclethra macrophylla Benth), Durian seed germination (Durio zibethinus L.), and rubber seeds (Hevea brasiliensis). Keywords : Seed lipase, characteristics, reaction mechanism